A positive temperature‐dependent effect of elevated CO 2 on growth and lipid accumulation in the planktonic copepod, Calanus finmarchicus - David M. Fields; Jeffrey A. Runge; Cameron R. S. Thompson; Caroline M. F. Durif; Steven D. Shema; Reidun M. Bjelland; Maura Niemisto; Michael T. Arts; Anne Berit Skiftesvik; Howard I. Browman (Limnology and Oceanography, 2023)
Calanus finmarchicus were reared from eggs to adults at 12°C and 16°C with non‐limiting food in combination with ambient (600 μ atm) and high (1100 μ atm) p CO 2 . These conditions are likely to be encountered by the species at the southern margins of its biogeographical range by the end of the century. Dry weight (DW), carbon (C) and nitrogen (N) mass, oil‐sac volume (OSV), fatty acid composition (FA), and oxygen consumption rates (OCR) were measured on newly molted stage CV copepodites and recently molted adult females. By focusing our measurements on these precise events in the life cycle, we were able to obtain a more accurate comparison of growth and respiration across treatments. Copepods raised at 12°C had a significantly greater DW, OSV, and C and N mass than those raised at 16°C High p CO 2 , independent of temperature, was associated with a further increase in the DW and C content of the copepods. Interactive effects of temperature and p CO 2 resulted in a larger OSV at low temperature and high p CO 2 . Mass‐specific respiration rates were significantly lower at lower temperatures and elevated p CO 2 suggesting that the increase in mass (DW, C, and OSV) resulted from reduced metabolic cost. The composition of fatty acids in the copepods varied mainly with temperature. Two fatty acids varied with p CO 2 : 16:0 tended to decrease with higher p CO 2 and 18:3n−3 tended to increase with higher p CO 2 . These observations suggest that elevated p CO 2 /lower pH in future oceans may have a beneficial effect on C. finmarchicus .

Co-exposure to UV radiation and crude oil increases acute embryotoxicity and sublethal malformations in the early life stages of Atlantic haddock (Melanogrammus aeglefinus) - Elin Sørhus; Carey E. Donald; Charlotte L. Nakken; Prescilla Perrichon; Caroline M.F. Durif; Steven Shema; Howard I. Browman; Anne Berit Skiftesvik; Kai K. Lie; Josef D. Rasinger; Mette H.B. Müller; Sonnich Meier (Science of The Total Environment, 2023)

Sub-lethal exposure to ultraviolet radiation reduces prey consumption by Atlantic cod larvae (Gadus morhua) - Yuichi Fukunishi; Howard I. Browman; Caroline M. F. Durif; Reidun M. Bjelland; Steven D. Shema; David M. Fields; Anne Berit Skiftesvik (Marine Biology, 2013)